KELAYAKAN TEORITIS LEMBAR KEGIATAN SISWA BERBASIS GUIDED DISCOVERY PADA MATERI SISTEM PENCERNAAN - NOERMA PURWANINGTYAS, RISKA (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2014)
Learning processes of biology in SMA use worksheets corresponding to the school environment and students reasoning level but they not facilitate students to concepts. Based are this reason, the research aims to produce worksheets based on Guided Discovery on the topic of human digestive system. The development of worksheets used 4D models and the worksheets were tried out to 30 students of class XI by design of One Shoot Case Study. Data analysis was conducted descriptively. The results of this research shows that the worksheets based on Guided Discovery are feasible with score 3,0 – 4,0. Keywords: worksheets, Guided Discovery, digestive system